The Struggle of Educating. And of Being “A Grown-up” - Zamengo, Federico (ETHICS IN PROGRESS, 2017)
In the face of contemporary educational transformations, this contribution aims to analyze the educational role that can still be played by the adult educator. Without restoring old categories of the past, today's adults continue to have a responsibility in the growth of younger generations. Accepting this task means first of all critically and reflectively recognizing one's role and, secondly, accepting the challenges posed by the complexity of today's landscape in terms of credibility and consistency.